Effect on nasopharyngeal pneumococcal carriage of replacing PCV7 with PCV13 in the Expanded Programme of Immunization in The Gambia. Issue 51 (16th December 2015) - ,; Oluwalana, Claire; Idoko, Olubukola; Cox, Isatou; Kwambana-Adams, Brenda A.; Jarju, Sheikh; Foster-Nyarko, Ebenezer; Greenwood, Brian; Roca, Anna; Bojang, Abdoulie; Bottomley, Christian; Gladstone, Rebecca A.; et al.
Abstract: Introduction: In 2011, two years after the introduction of 7-valent Pneumococcal conjugate vaccine (PCV7), the Gambian immunization programme replaced PVC7 with PCV13 (13-valent). Our objective was to assess the additional impact of PCV13 on prevalence of pneumococcal nasopharyngeal carriage. Methods: We recruited healthy Gambian infants who had received three PCV doses. Nasopharyngeal swabs were collected from infants and their mothers during two cross-sectional surveys (CSS) conducted in infants vaccinated with PCV7 (CSS1) and vaccinated with PCV13 (CSS2). Pneumococci were isolated and serotyped following standardized methods. Whole genome sequencing was performed on non-typable pneumococcus isolated in CSS1 and CSS2. Results: 339 and 350 infants and their mothers were recruited in CSS1 and CSS2, respectively. Overall prevalence of pneumococcal carriage was 85.4% in infants. Among infants, prevalence of vaccine type (VT) carriage was lower in CSS2 [9.4% versus 4.9% ( p = 0.025) for PCV7-VT; 33.3% versus 18.3% ( p < 0.001) for PCV13-VT and 23.9% versus 13.7% ( p = 0.001) for the 6 additional serotypes included in PCV13]. At CSS2, there was a decrease of serotypes 6A (from 15.3% to 5.7%, p < 0.001) and 19F (from 5.6% to 1.7%, p = 0.007), and an increase of non-typable pneumococci (0.3–6.0%, p < 0.001), most of which (82.4%) were from typable serotype backgrounds that had lost the ability to express a capsule. Prevalence of overall and VT carriage in mothers was similar in CSS1 and CSS2. Conclusions: Replacing PCV7 for PCV13 rapidly decreased prevalence of VT carriage among vaccinated Gambian infants. An indirect effect in mothers was not observed yet. Vaccine-driven selection pressure may have been responsible for the increase of non-typable isolates.